Antioxidative status and oxidative stress in the fetal circulation at birth: the effects of time of delivery and presence of labor. Issue 2 (February 2015) - Katzer, David; Mueller, Andreas; Welzing, Lars; Reutter, Heiko; Reinsberg, Jochen; Bartmann, Peter; Bagci, Soyhan
Abstract Background : There are important physiological changes in the maternal, placental, and fetal compartments during pregnancy and labor. Increased oxidative stress has been demonstrated during labor. Melatonin has been reported to serve as an indirect antioxidant via the stimulation and induction of antioxidant enzymes as superoxide dismutase (SOD) and glutathione peroxidase (Gpx) in several tissues. Aim : To assess whether the melatonin status, presence of labor at the time of birth and the time of delivery influence the extracellular antioxidative enzymes and DNA oxidative stress in newborns. Methods : The extracellular antioxidative status and oxidative stress were analyzed by measuring the concentrations of the SOD3, Gpx3 and 8-hydroxydeoxyguanosine (8-OHdG) in the cord blood of 135 newborns. Newborns delivered during the day and at night and newborns delivered by spontaneous vaginal delivery (labor group) or elective caesarean section delivery (no labor group) were studied. Outcome measures : The concentration of melatonin, SOD3, Gpx3 and 8-OHdG. Results : Independent of the time of delivery, we found significantly higher melatonin, SOD3 and Gpx3 but lower 8-OHdG concentrations in the labor group than in the no labor group. We did not observe a correlation between the concentration of melatonin and SOD3, Gpx3 or 8-OHdG, or a day–night difference in SOD3, Gpx3 or 8-OHdG. Conclusion : Our findings suggest that oxidative stress during labor leads to an elevation of melatonin, SOD3 and Gpx3 in the fetal circulation, protecting the newborn from serious impairment, which is reflected by lower 8-OHdG levels. The melatonin status at the time of birth does not influence the extracellular SOD3 or Gpx3 concentrations.